Effect of subtherapeutic and therapeutic sulfamethazine concentrations on transcribed genes and translated proteins involved in Microbacterium sp. C448 resistance and degradation - Paris, Laurianne; Devers-Lamrani, Marion; Joly, Muriel; Viala, Didier; De Antonio, Marie; Pereira, Bruno; Rouard, Nadine; Besse-Hoggan, Pascale; Hébraud, Michel; Topp, Edward; Martin-Laurent, Fabrice; Batisson, Isabelle (FEMS microbiology ecology, 2023)
Abstract Microbacterium sp. C448, isolated from a soil regularly exposed to sulfamethazine (SMZ), can use various sulphonamide antibiotics as the sole carbon source for growth. The basis for the regulation of genes encoding the sulphonamide metabolism pathway, the dihydropteroate synthase sulphonamide target (folP), and the sulphonamide resistance (sul1) genes is unknown in this organism. In the present study, the response of the transcriptome and proteome of Microbacterium sp. C448 following exposure to subtherapeutic (33 µM) or therapeutic (832 µM) SMZ concentrations was evaluated. Therapeutic concentration induced the highest sad expression and Sad production, consistent with the activity of SMZ degradation observed in cellulo. Following complete SMZ degradation, Sad production tended to return to the basal level observed prior to SMZ exposure. Transcriptomic and proteomic kinetics were concomitant for the resistance genes and proteins. The abundance of Sul1 protein, 100-fold more abundant than FolP protein, did not change in response to SMZ exposure. Moreover, non-targeted analyses highlighted the increase of a deaminase RidA and a putative sulphate exporter expression and production. These two novel factors involved in the 4-aminophenol metabolite degradation and the export of sulphate residues formed during SMZ degradation, respectively, provided new insights into the Microbacterium sp. C448 SMZ detoxification process. Transcriptomic and proteomic responses of Microbacterium sp. C448 exposed to sulfamethazine antibiotic.